Las donaciones a España del obispo de Quito don Diego Ladrón de Guevara - Justo Estebaranz, Ángel (Artigrama, 2009)
ResumenEn los primeros años del siglo XVIII, el XIII obispo de Quito, don Diego Ladrón de Guevara, hace diversas donaciones a Castilla, de donde procedía. Éstas consistían en elevadas cantidades de dinero y piezas de platería y joyería de importante valor, que iban destinadas tanto a aumentar el Mayorazgo de Orozco, que el prelado poseía en Hita, como a personas particulares e iglesias con las que había tenido relación durante sus años en la Península Ibérica. Esta actitud es típica de quienes, durante la época virreinal, prosperaban en Indias y querían agradecer a la Iglesia y a sus allegados la buena fortuna de que disfrutaban. En este artículo se analiza documentación inédita procedente de archivos quiteños y españoles sobre las donaciones que efectúa el obispo y el envío de las mismas a la metrópoli.In the first years of the 18th century, the XIII bishop of Quito don Diego Ladrón de Gue-vara makes diverse donations to Castilla, wherefrom it he was coming. These were consisting of high quantities of money, as well as pieces of silverwork and jewellery of important value, which were destined to increase so much Orozco’s Primogeniture that the prelate was possessing in Hita as to particular persons and churches with which it he had had relation for his years in the Iberian Peninsula. This attitude is typical of whom, during the viceregal epoch, they were prospering in The Indies and wanted to be grateful to the Church and to his relatives for the good fortune that they were enjoying. In this paper we analyze unpublished documentation proceeding from of Quitean and Spanish files on the donations that there effects the bishop and the sending of the same ones to the Metropolis.Palabras claveDiego Ladrón de Guevara, Quito, donaciones, platería, siglo XVIII.Diego Ladrón de Guevara, Quito, gifts, silver, eighteenth century.